Audit Fees, Auditor Specialization, Time Budget Pressure, and KAP Sizes on Audit Quality - Galuh Chandra Rheisyta Putri; Bestari Dwi Handayani (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Using KAP sizes as a moderating variable, this study attempts to examine the impact of audit fees, auditor specialisation, and time-budget pressure on audit quality. This study analyzes secondary data from annual reports of companies listed on the Indonesia Stock Exchange (IDX) from 2022 to 2024, using a quantitative approach. The purposively selected sample includes 38 companies with 114 data points. Moderated regression analysis (MRA) was conducted using SPSS 26. The results indicate that audit quality is not influenced by audit fees, auditor specialization, or time-budget constraints. Furthermore, the relationship between audit quality and these independent variables remains unaffected by KAP sizes. The results indicate that other components, such as compliance with audit standards, auditor independence, and the quality control system of the Public Accounting Firm, have a greater influence on audit quality.